Investigation of the Relationship Between Texture Coefficient and Electrical Current Consumption of the Cutting Machine with Different Lubricants and Cooling Fluids (Journal of Global Humanities and Social Sciences, 2024)
Texture coefficient (TC) is one of the most effective physical factors in evaluating the engineering characteristics of rocks in various projects, such as drilling, cutting, and advanced rate of full-face drilling machines. Evaluation of electricity consumption by disccutting machines is critical for monitoring and reducing expenses in the stone processing industry. In this study, the relationship between the textural characteristics of the rocks and the amount of electrical current consumed by the cutting machine in cutting hard stones was evaluated. For this purpose, ten samples of hard rock were investigated. For each rock sample, a microscopic slice was prepared. Then, five digital images were taken using the microscope from each division, and the values of textural characteristics, including area, perimeter, largest diameter, and most minor diameter of all grains in each embodiment, were determined. Then, the TC of all studied stone samples was computed based on the determined specifications. Finally, the relationship between the TC and the rate of electrical current consumed by the cutting machine was investigated using statistical models. The results revealed that although the electric current used by the cutting machine decreased when the TC increased in some samples, no significant relationship between the TC and the amount of electric current used by the cutting machine was observed for hard stone samples. It was also found that the impact of lubricant type on the cutting machine performance is negligible.